2022
DOI: 10.31955/mea.v6i3.2501
|View full text |Cite
|
Sign up to set email alerts
|

Do Personalities and Motivation Affect Job Performance? An Evidence From a Rural Bank in Central Java

Abstract: Good employee performance is the main thing for the company. Poor performance will cause the company to suffer losses, or it can even experience bankruptcy and liquidation. Until now, many rural banks in Indonesia are experiencing liquidation, so it is necessary to find a solution to improve the performance of rural bank employees in Indonesia so that liquidation can be avoided. This research aims to examine whether the big five personalities of employees and employee motivation can affect job performance. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…An individual's employee motivation is closely related to the performance that individuals produce when carrying out their jobs. The findings are supported by (Subiyanto et al, 2022), (Tamrin, 2021), and (Prabowo & Yulianti, 2022), which state that employee motivation has a positive and significant effect on job performance. As a result, the following hypothesis is proposed in this study: H3: There is a significant effect of employee motivation on job performance.…”
Section: The Effect Of Employee Motivation On Job Performancementioning
confidence: 71%
See 1 more Smart Citation
“…An individual's employee motivation is closely related to the performance that individuals produce when carrying out their jobs. The findings are supported by (Subiyanto et al, 2022), (Tamrin, 2021), and (Prabowo & Yulianti, 2022), which state that employee motivation has a positive and significant effect on job performance. As a result, the following hypothesis is proposed in this study: H3: There is a significant effect of employee motivation on job performance.…”
Section: The Effect Of Employee Motivation On Job Performancementioning
confidence: 71%
“…Previous research has shown that employee motivation has a significant effect on job performance (Forson et al, 2021). Similarly, research by (Prabowo & Yulianti, 2022), but (Panjaitan & Kustiawan, 2022); (Wijsman et al, 2018) claims that employee motivation has no effect on job performance.…”
Section: Introductionmentioning
confidence: 93%